The making of the "Rape of Nanking" - Takashi Yoshida (Oxford University Press, 2006)
The Making of the "Rape of Nanking" Takashi Yoshida examines how views of the Nanjing Massacre have evolved in history writing and public memory in Japan, China, and the United States. For these nations, the question of how to treat the legacy of Nanjing--whether to deplore it, sanitize it, rationalize it, or even ignore it--has aroused passions revolving around ethics, nationality, and historical identity. Drawing on a rich analysis of Chinese, Japanese, and American history textbooks and newspapers, Yoshida traces the evolving--and often conflicting--understandings of the Nanjing Massacre, revealing how changing social and political environments have influenced the debate. Yoshida suggests that, from the 1970s on, the dispute over Nanjing has become more lively, more globalized, and immeasurably more intense, due in part to Japanese revisionist history and a renewed emphasis on patriotic education in China